"A Different Atmosphere of Love": A Qualitative Study of the Experiences of Participants in Evangelical Substance User Rehabilitation Programs in the Russian Federation. (23rd April 2013) - Stoltzfus, Kenneth M.; Cecil, David
<x xml:space="preserve">Abstract</x> This article explores the lived experiences of individuals who have participated in faith-based substance user rehabilitation programs in the Russian Federation. The Russian Federation has high rates of alcohol and opioid dependence and a dearth of professional treatment options. In the post-Soviet period, Evangelical Christian groups have developed substance user rehabilitation programs to attempt to address substance use and its related problems. Data were collected during 2010 via focus group interviews with participants in three Evangelical rehabilitation programs in the Volga region of the Russian Federation. Themes emerging from the qualitative data analysis process were classified into three broad categories: Typical Day, Personal Background/Decision to Enter Rehabilitation, and Helpful Aspects of Rehabilitation Process.